A fast quadtree‐based terrain crack locating method that accounts for adjacency relationships. Issue 6 (30th September 2019) - Li, Chengming; Zhao, Zhanjie; Sun, Wei; Liu, Zhendong
Abstract: The repair of terrain cracks is an important process in multi‐resolution three‐dimensional terrain visualization, and rapid and accurate pinpointing of cracks between terrain blocks is of the utmost importance for this process. The existing quadtree‐based crack locating methods are generally slow and inefficient, as they require the traversal of terrain quadtrees to locate terrain cracks. In this research, we propose a fast quadtree‐based terrain crack locating method that accounts for adjacency information. First, terrain quadtrees are constructed that contain information regarding adjacency relationships. Second, dynamic updating is performed for terrain quadtrees and their adjacency information. Finally, terrain cracks are located by using the adjacencies of the quadtree nodes. This proposed method was experimentally validated via the terrain data of a mountainous region in Sichuan Province. The experimental results indicate that the proposed method can be used to efficiently and accurately locate terrain cracks with a strong performance in practical applications.